2008
DOI: 10.1182/blood-2007-08-109611
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia infection and risk of non-Hodgkin lymphoma

Abstract: Reports of the presence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 47 publications
0
49
0
2
Order By: Relevance
“…Similarly, no significant association with latitude band was observed for NHL NOS (ICD-O-3 9591, 9675, 9684, 9832; n 5 3,001; p 5 0.171); relative to <29 S, the IRRs were 1.67 (95% CI: 1.46-1.93) for [29][30][31][32][33][34][35][36] S and 0.88 (95% CI: 0.74-1.05) for 37 S for NHL NOS (data not shown in figure). There were 2,418 cases of HL registered during the study period, 2,300 (95%) of which were classical HL and 118 (5%) of which were nodular lymphocyte predominant HL (NLPHL).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, no significant association with latitude band was observed for NHL NOS (ICD-O-3 9591, 9675, 9684, 9832; n 5 3,001; p 5 0.171); relative to <29 S, the IRRs were 1.67 (95% CI: 1.46-1.93) for [29][30][31][32][33][34][35][36] S and 0.88 (95% CI: 0.74-1.05) for 37 S for NHL NOS (data not shown in figure). There were 2,418 cases of HL registered during the study period, 2,300 (95%) of which were classical HL and 118 (5%) of which were nodular lymphocyte predominant HL (NLPHL).…”
Section: Resultsmentioning
confidence: 98%
“…Bacterial infection, evidenced by antibiotic use, might also be important in CLL/SLL pathogenesis. 43 Some under-notification of CLL laboratory diagnoses has been identified in New South Wales, 44 a large Australian state falling within the central latitude band (29)(30)(31)(32)(33)(34)(35)(36) S) in our study. Any systematic geographical variation in reporting by pathology laboratories will have influenced our findings for this neoplasm.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An important aspect to keep in mind when interpreting our results is that our testing methods are virtually the same as the Scandinavian case-control study which reported a statistically significant association between anti-Borrelia seropositivity and the risk of developing mantle cell lymphoma. 3 Added advantages in our study include the prospective study design, which eliminates recall bias, and the ability to evaluate the risk of all malignancies. We carried out a thorough analysis and interpreted our results with caution.…”
Section: To the Editormentioning
confidence: 99%
“…1,2 Importantly, the recent Scandinavian case-control study, which observed a statistically significant association between anti-Borrelia seropositivity and risk of mantle cell lymphoma used a similar in-house ELISA test 3 with the same estimated sensitivity. On a statistical note, low sensitivity of a test generally leads to nondifferential misclassification leading to bias toward the null value.…”
Section: To the Editormentioning
confidence: 99%